(untitled) (Philologia, 2021)
Feminists have long condemned the trivialisation and sexualisation of women in British newspapers but have perhaps focused too little on what sometimes appears to be a veritable demonisation of high-profile women. For example, the death of Amy Winehouse in summer 2011 seems prima facie not entirely unrelated to the years of vilification she was subjected to, especially in The Sun. This study therefore conducts a comparative examination into the Othering of Heather Mills, ex-wife of Paul McCartney, in parallel articles from The Sun and The Guardian. To produce a multilayered linguistic analysis we employ a range of functional-grammatical tools: transitivity to compare the roles allotted to Mills and McCartney; nomination to see how they are named; categorisation regarding the stereotypes with which they are associated; and appraisement to show whether they are depicted positively or negatively. The results suggest that there is a serious imbalance in the portrayal of these two celebrities. We ask why this might be. Is Mills that monstrous, McCartney that angelic? Or is it that a divorce scenario, pitting hero against villain, provides a perfect vehicle for indirect dissemination of the newspaper’s ideology and the expression of a pre-existing message?